Metabolism Regulates Cellular Functions of Bone Marrow‐Derived Cells used for Cardiac Therapy. (25th May 2016) - Derlet, Anja; Rasper, Tina; Roy Choudhury, Aaheli; Bothur, Sabrina; Rieger, Michael A.; Namgaladze, Dmitry; Fischer, Ariane; Schürmann, Christoph; Brandes, Ralf P.; Tschulena, Ulrich; Steppan, Sonja; Assmus, Birgit; et al.
Abstract: Administration of bone marrow‐derived mononuclear cells (BMC) may increase cardiac function after myocardial ischemia. However, the functional capacity of BMC derived from chronic heart failure (CHF) patients is significantly impaired. As modulation of the energy metabolism allows cells to match the divergent demands of the environment, we examined the regulation of energy metabolism in BMC from patients and healthy controls (HC). The glycolytic capacity of CHF‐derived BMC is reduced compared to HC, whereas BMC of metabolically activated bone marrow after acute myocardial infarction reveal increased metabolism. The correlation of metabolic pathways with the functional activity of cells indicates an influence of metabolism on cell function. Reducing glycolysis without profoundly affecting ATP‐production reversibly reduces invasion as well as colony forming capacity and abolishes proliferation of CD34 + CD38 − lin − hematopoietic stem and progenitor cells (HSPC). Ex vivo inhibition of glycolysis further reduced the pro‐angiogenic activity of transplanted cells in a hind limb ischemia model in vivo. In contrast, inhibition of respiration, without affecting total ATP production, leads to a compensatory increase in glycolytic capacity correlating with increased colony forming capacity. Isolated CD34 +, CXCR4 +, and CD14 + cells showed higher glycolytic activity compared to their negative counterparts. Metabolic activity was profoundly modulated by the composition of media used to store or culture BMC. This study provides first evidence that metabolic alterations influence the functional activity of human HSPC and BMC independent of ATP production. Changing the balance between respiration and glycolysis might be useful to improve patient‐derived cells for clinical cardiac cell therapy. Stem Cells 2016;34:2236–2248 Abstract : Cell therapy using bone marrow‐derived mononuclear cells (BMC) may increase cardiac function after myocardial ischemia. However, cardiovascular disease significantly affects functional capacity of BMC as well as seems to induce a specific metabolic alteration. Metabolic modification can affect cell function measured as colony formation and proliferation as well as outcome after cell therapy measured in a hind limb ischemia model.